The Past and Memory in "Archive of Lives": Justyna Łuczaj-Salefs Impressionist Historical Documentary - Czaja, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The documentary film Archiwum istnień tells the story of research by Nazi anthropologists searching among the population of occupied Poland for representatives of the Aryan race. In her film, the director makes use of archival materials from World War Two (above all, photographs, propaganda film chronicles and letters). Not only does Justyna Łuczaj-Salej incorporate the above into the cinematographer’s box of tricks, but most of all, she exploits them counter to their authors’ intentions, thereby initiating a process that de-contextualises and re-contextualises these archives in a deconstruction of the past.